Consequences of Non-Compliance with Technological Procedures in the Realisation of Construction Objects from the Point of View of Heat Consumption for Heating—A Case Study on Selected Construction Sites in the Slovak Republic - Ján Hlina; Peter Makýš; Patrik Šťastný; Lucia Paulovičová (Energies)
This article focuses on the energy performance of buildings with an emphasis on the consequences of non-compliance with technological practices during the building process. We analyse the impact of construction deficiencies on the consumption of heat for heating, focusing on specific case studies of selected building constructions in the Slovak Republic. The results show that non-compliance with prescribed technological standards and procedures leads to significant deterioration in the building’s energy efficiency, which is manifested in increased heat consumption and higher operating costs. The findings of this study have key importance for future construction projects as they offer valuable recommendations for improving energy standards and construction quality, thus contributing to a more sustainable and efficient building process. When designing buildings with near-zero energy demand, it is necessary to eliminate all risks in the project that arise during the preparation and design itself, as well as during implementation.